2011
DOI: 10.1007/s12038-011-9006-4
|View full text |Cite
|
Sign up to set email alerts
|

Is endothelial-nitric-oxide-synthase-derived nitric oxide involved in cardiac hypoxia/reoxygenation-related damage?

Abstract: Nitric oxide (NO) has been reported to act both as a destructive and a protective agent in the pathogenesis of the injuries that occur during hypoxia/reoxygenation (H/R). It has been suggested that this dual role of NO depends directly on the isoform of NO synthase (NOS) involved. In this work, we investigate the role that NO derived from endothelial NOS (eNOS) plays in cardiac H/R-induced injury. Wistar rats were submitted to H/R (hypoxia for 30 min; reoxygenation of 0 h, 12 h and 5 days), with or without pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
5
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 52 publications
2
5
0
Order By: Relevance
“…However, the effect of iNOS inhibition is contradictory and might be organ and cell type specific. In hypoxic lung injury, selective iNOS inhibition has been shown to attenuate hypoxia-induced lung injury (39), whereas in cardiac I/R injury, the same iNOS inhibitor exacerbated peroxidative and apoptotic damage (39,40). In the present study, the diminished renal iNOS expression in PKC-ε-deficient allografts was accompanied by protective effects with less inflammation and apoptosis.…”
Section: Discussionsupporting
confidence: 47%
“…However, the effect of iNOS inhibition is contradictory and might be organ and cell type specific. In hypoxic lung injury, selective iNOS inhibition has been shown to attenuate hypoxia-induced lung injury (39), whereas in cardiac I/R injury, the same iNOS inhibitor exacerbated peroxidative and apoptotic damage (39,40). In the present study, the diminished renal iNOS expression in PKC-ε-deficient allografts was accompanied by protective effects with less inflammation and apoptosis.…”
Section: Discussionsupporting
confidence: 47%
“…AOM supplementation induced the accumulation of free radicals and increased the intracellular level of apoptotic-sensitive proteins. The free radical scavenging mechanism involves oxidative-mediated apoptosis, which requires ferric acid reduction; therefore, the production of NO and iNOS is regulated 31 . S. crispus at an IC50 of 5.44 + 1.76 effectively inhibited DPPH free radicals, nitric oxide and ferric reduction sequences.…”
Section: Discussionmentioning
confidence: 99%
“…First, hCG augments superoxide dismutase 2 expression via FOXO1, thereby enhancing the free radicalscavenging potential and second, hCG inhibited the expression of the proapoptotic Bax protein and up-regulated antiapoptotic Bcl-2 [Kajihara et al 2011]. Moreover, studies in other tissues indicated that an increase in apoptosis is in line with a rise in NO levels during cardiac hypoxiareoxygenation [Rus et al 2011] and renal ischaemiahypoxia-reoxygenation [Viñas et al 2006].…”
Section: Discussionmentioning
confidence: 99%
“…NO may exert pro-oxidant effects by reducing ferric iron complexes, thereby inducing a release of bound iron and indirectly substituting for other reductants in the Haber-Weiss reaction-mediated production of HO from H 2 O 2 . Furthermore, peroxynitrite derived from NO can induce lipid peroxidation in model systems without iron participation [Radi et al 1991;Rus et al 2011]. Additionally, the presence of nitrative stress was associated with diminished vascular reactivity of the fetal placental circulation, a situation that could be reproduced by treatment with peroxynitrite in vitro [Myatt 2010].…”
Section: Discussionmentioning
confidence: 99%